2011
DOI: 10.1016/j.jfa.2010.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Power boundedness in Fourier and Fourier–Stieltjes algebras and other commutative Banach algebras

Abstract: We study power boundedness in the Fourier and Fourier-Stieltjes algebras, A(G) and B(G), of a locally compact group G as well as in some other commutative Banach algebras. The main results concern the question of when all elements with spectral radius at most one in any of these algebras are power bounded, the characterization of power bounded elements in A(G) and B(G) and also the structure of the Gelfand transform of a single power bounded element.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In view of (13) and the preceding discussion, one expects an estimate of the form (14) to hold for φ (n) , although, we note that no such estimate can be established on these grounds (this is due to the error term in (13)). This however motivates the correct form and we are able to establish the following result which captures, as a special case, the situation described above in which Ω(φ) = {ξ 0 }.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…In view of (13) and the preceding discussion, one expects an estimate of the form (14) to hold for φ (n) , although, we note that no such estimate can be established on these grounds (this is due to the error term in (13)). This however motivates the correct form and we are able to establish the following result which captures, as a special case, the situation described above in which Ω(φ) = {ξ 0 }.…”
Section: Introductionmentioning
confidence: 74%
“…For an approximate difference scheme to an initial value problem, the property (1) is necessary and sufficient for convergence to a classical solution; this is the so-called Lax equivalence theorem [18] (see Section 6). Property (1) is also called power boundedness and can be seen in the context of Banach algebras where φ is an element of the Banach algebra ( 1 (Z d ), • 1 ) equipped with the convolution product [14,21].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it is shown that if u is a power bounded element of B(G), then the set of all x in G such that u(x) = 1 is in the closed coset ring of G, which was completely characterized by Forrest [9] (and previously by Gilbert [13] and Schreiber [40] in the abelian case). Further related investigations are carried out in the articles [19] and [20], continuing Tony's collaboration with E. Kaniuth and A.Ülger.…”
Section: Multipliers Of Commutative Banach Algebras With Applications Tomentioning
confidence: 99%
“…In the first case, by [24, Proposition 1.1], γ extends to some continuous positive definite function σ on G, and so λσ is the required extension of u. Alternatively, instead of using [24], we could proceed as follows. Since |u(x)| = 1 for all x ∈ G 0 , by [21,Proposition 4.5] either u is constant or w * -lim n→∞ u n = 0. Therefore, to establish the theorem, we have to show that if w * -lim n→∞ u n = 0, then there exists w ∈ B(G) such that w| G 0 = u and w * -lim n→∞ w n = 0.…”
Section: This Formula In Turn Impliesmentioning
confidence: 99%
“…for all n. It therefore suffices to verify that v is also power bounded. This can be done by using precisely the same arguments as in the proof of [21,Theorem 3.4].…”
mentioning
confidence: 99%